Pemetaan Pendidikan karakter Melalui Hafalan Juz ‘Amma di MI Ma’arif Soka Poncowarno - Rohimah, Hikmatul Ali; Chamidi, Agus Salim (IAINU Kebumen, 2024)
Mapping character education through memorizing juz 'amma at Mi Ma'arif Soka Poncowarno.This study aims (1) to find out what character education appears in the juz 'amma memorizationmapping activity at Mi Ma'arif Soka (2) to find out what character education is most prominent inthe juz 'amma memorization mapping activity at Mi Ma' soka wise. This research is in the form offield research. His research used a qualitative approach. The subjects in this study were the headof the madrasa, class teacher, tahfdz teacher at Mi Ma'arif Soka. Data collection methods usedwere observation, interviews, documentation and data triangulation. While the data analysistechnique uses data reduction, data presentation, and drawing conclusions. The results of this studycan be concluded that: (1) character education that appears in the memorization of juz 'amma atMi Ma'arif Soka: religious attitude, honest, disciplined, hard work, independent,friendly/communicative, and responsible. (2) the most prominent character education in thememorization of juz 'amma in Mi Ma'arif soka: religious, honest, disciplined